Night Sky Brightness at San Pedro Martir Observatory. (2nd February 2017) - Plauchu-Frayn, I.; Richer, M. G.; Colorado, E.; Herrera, J.; Córdova, A.; Ceseña, U.; Ávila, F.
Abstract: We present optical UBVRI zenith night sky brightness measurements collected on 18 nights during 2013 to 2016 and SQM measurements obtained daily over 20 months during 2014 to 2016 at the Observatorio Astronómico Nacional on the Sierra San Pedro Mártir (OAN-SPM) in México. The UBVRI data is based upon CCD images obtained with the 0.84 m and 2.12 m telescopes, while the SQM data is obtained with a high-sensitivity, low-cost photometer. The typical moonless night sky brightness at zenith averaged over the whole period is U = 22.68, B = 23.10, V = 21.84, R = 21.04, I = 19.36, and SQM = 21.88 mag arcsec − 2, once corrected for zodiacal light. We find no seasonal variation of the night sky brightness measured with the SQM. The typical night sky brightness values found at OAN-SPM are similar to those reported for other astronomical dark sites at a similar phase of the solar cycle. We find a trend of decreasing night sky brightness with decreasing solar activity during period of the observations. This trend implies that the sky has become darker by Δ U = 0.7, Δ B = 0.5, Δ V = 0.3, Δ R = 0.5 mag arcsec −2 since early 2014 due to the present solar cycle.